Prenatal Iron Supplementation Reduces Maternal Anemia, Iron Deficiency, and Iron Deficiency Anemia in a Randomized Clinical Trial in Rural China, but Iron Deficiency Remains Widespread in Mothers and Neonates(1)(2)(3) - Zhao, Gengli (J Nutr, 2015)
Background: Previous trials of prenatal iron supplementation had limited measures of maternal or neonatal iron status. Objective: The purpose was to assess effects of prenatal iron-folate supplementation on maternal and neonatal iron status. Methods: Enrollment occurred June 2009 through December 2011 in Hebei, China. Women with uncomplicated singleton pregnancies at ≤20 wk gestation, aged ≥18 y, and with hemoglobin ≥100 g/L were randomly assigned 1:1 to receive daily iron (300 mg ferrous sulfate) or placebo + 0.40 mg folate from enrollment to birth. Iron status was assessed in maternal venous blood (at enrollment and at or near term) and cord blood. Primary outcomes were as follows: 1) maternal iron deficiency (ID) defined in 2 ways as serum ferritin (SF) <15 μg/L and body iron (BI) <0 mg/kg; 2) maternal ID anemia [ID + anemia (IDA); hemoglobin <110 g/L]; and 3) neonatal ID (cord blood ferritin <75 μg/L or zinc protoporphyrin/heme >118 μmol/mol). Results: A total of 2371 women were randomly assigned, with outcomes for 1632 women or neonates (809 placebo/folate, 823 iron/folate; 1579 mother-newborn pairs, 37 mothers, 16 neonates). Most infants (97%) were born at term. At or near term, maternal hemoglobin was significantly higher (+5.56 g/L) for iron vs. placebo groups. Anemia risk was reduced (RR: 0.53; 95% CI: 0.43, 0.66), as were risks of ID (RR: 0.74; 95% CI: 0.69, 0.79 by SF; RR: 0.65; 95% CI: 0.59, 0.71 by BI) and IDA (RR: 0.49; 95% CI: 0.38, 0.62 by SF; RR: 0.51; 95% CI: 0.40, 0.65 by BI). Most women still had ID (66.8% by SF, 54.7% by BI). Adverse effects, all minor, were similar by group. There were no differences in cord blood iron measures; >45% of neonates in each group had ID. However, dose-response analyses showed higher cord SF with more maternal iron capsules reported being consumed (β per 10 capsules = 2.60, P < 0.05). Conclusions: Prenatal iron supplementation reduced anemia, ID, and IDA in pregnant women in rural China, but most women and >45% of neonates had ID, regardless of supplementation. This trial was registered at clinicaltrials.gov as NCT02221752.